An insight into the role of side chains in the microstructure and carrier mobility of high-performance conjugated polymers. Issue 16 (7th April 2021) - Pan, Yuchai; Huang, Jianyao; Gao, Dong; Chen, Zhihui; Zhang, Weifeng; Yu, Gui
Abstract : The effect of linear-chain interdigitation on device performance was studied in detail by both experimental and theoretical methods. Abstract : Semiconducting polymers are important electronic materials for both industrial and academic purposes. The structure–performance relationship of semiconducting polymers is still a research frontier of ongoing interest. Structural engineering is crucial to develop new semiconducting polymers with enhanced properties. Due to their combination of high processability and performance, multi-alkylated conjugated polymers are emerging as a hot research topic. In this work, a series of diketopyrrolopyrrole-based polymers with different alkyl chain lengths, PD-8-DTTE- n, were prepared to investigate the relationship between the microstructure and charge transport properties in a multi-alkylated system. The electrical performance shows a strong correlation with the alkyl side chain. The hole mobility of this series of diketopyrrolopyrrole-based copolymers increased with increasing length of the linear alkyl side chain, and OFETs based on the polymer with the longest linear side chain (undecyl) led to the highest hole mobility of 1.10 cm 2 V −1 s −1 . Surface morphology and thin-film microstructure are related to the enhanced charge transport properties. Molecular mechanics/molecular dynamics simulations were used to analyze the microstructure information. These studies collectively rationalize the relationship between the molecular structure, microstructure, and film morphology from a molecular to a macroscopic level, and give a comprehensive understanding of design rules for such high-performance semiconductor materials.